Competency-based cardiac imaging for patient-centred care. A statement of the European Society of Cardiology (ESC). With the contribution of the European Association of Cardiovascular Imaging (EACVI), and the support of the Association of Cardiovascular Nursing & Allied Professions (ACNAP), the Association for Acute CardioVascular Care (ACVC), the European Association of Preventive Cardiology (EAPC), the European Association of Percutaneous Cardiovascular Interventions (EAPCI), the European Heart Rhythm Association (EHRA), and the Heart Failure Association (HFA) of the ESC. - Westwood, Mark; Almeida, Ana G.; Barbato, Emanuele; Delgado, Victoria; Dellegrottaglie, Santo; Fox, Kevin F.; Gargani, Luna; Huber, Kurt; Maurovich-Horvat, Pál; Merino, Jose L.; Mindham, Richard; Muraru, Denisa; et al. (European Heart Journal, 2023)
Imaging plays an integral role in all aspects of managing heart disease and cardiac imaging is a core competency of cardiologists. The adequate delivery of cardiac imaging services requires expertise in both imaging methodology-with specific adaptations to imaging of the heart-as well as intricate knowledge of heart disease. The European Society of Cardiology (ESC) and the European Association of Cardiovascular Imaging have developed and implemented a successful education and certification programme for all cardiac imaging modalities. This programme equips cardiologists to provide high quality competency-based cardiac imaging services ensuring they are adequately trained and competent in the entire process of cardiac imaging, from the clinical indication via selecting the best imaging test to answer the clinical question, to image acquisition, analysis, interpretation, storage, repository, and results dissemination. This statement emphasizes the need for competency-based cardiac imaging delivery which is key to optimal, effective and efficient, patient care.
EVALuna2:583636